In vitro multiplication of woody bamboo in the Southwestern Amazon, Acre State, Brazil (Research, Society and Development, 2022)
Bamboos from the genus Guadua in the Southwestern Amazon basin are difficult to propagate because of their recalcitrant characteristics. This study aimed to evaluate the action of 6-benzylaminopurine (BA) during in vitro multiplication of G. latifolia in a laboratory for clonal seedling production. In vitro multiplication was performed using the cytokinin 6-benzylaminopurine at concentrations of 0, 2, 4, 6, 8 mg L-1 in glass tubes containing liquid medium, incubated for 38 days. The analyzed variables were shoot height, number of shoots, multiplication rate, and the presence of callus and roots in two consecutive subcultures. The use of 6-benzylaminopurine during in vitro multiplication was effective at increasing the number of shoots in the first and second subculture. Shoot height was not influenced by the cytokinin in the culture with a maximum multiplication rate of 4.44 shoots. Therefore, the use of 6 mg L-1 of BA is recommended during in vitro multiplication and to obtain a high multipication rate.